Characterization of Cardiac, Vascular, and Metabolic Changes in Young Childhood Cancer Survivors - Broberg, Olof; Øra, Ingrid; Wiebe, Thomas; Weismann, Constance G.; Liuba, Petru (Frontiers in Pediatrics, 2021)
Abstract Background: Childhood cancer survivors (CCS) are at increased risk for cardiovascular disease (CVD). It was the primary aim of this study to determine different measures of cardiac, carotid, lipid and apolipoprotein status in young adult CCS and in controls. Methods: Cardiac and common carotid artery (CCA) structure and function were measured by ultrasonography. Lipids and apolipoproteins were measured in the blood. Peripheral arterial endothelial vasomotor function was assessed by measuring digital reactive hyperemia index (PAT-RHI) using the Endo-PAT 2000. Results: 53 CCS (20–30 years, 35 men) and 53 sex-matched controls were studied. The CCS cohort was divided by the median dose of anthracyclines into a low anthracycline dose (LAD) group (50-197 mg/m2, n=26) and a high anthracycline dose (HAD) group (200-486 mg/m2, n=27). Carotid distensibility index (DI) and endothelial function determined by PAT-RHI were both lower in CCS groups compared to controls (p<0.05 and p=0.02). There was no difference in carotid intima media thickness. Atherogenic Apolipoprotein-B (Apo-B) and the ratio between Apo-B and Apoliprotein-A1 (Apo-A1) were higher in the HAD group compared to controls (p<0.01). Apo-B/Apo-A1-ratio was over reference limit in 29.6 % of HAD group, in 15.4% of LAD group and in 7.5% of controls (p=0.03). Measured lipid markers (low density lipoprotein and total cholesterol and triglycerides) were higher in both CCS groups compared to controls (p<0.05). Systolic and diastolic function were measurably impaired in the HAD group as evidenced by lower EF (p<0.001) and lower é-wave (p<0.005) compared to controls. Interestingly, CCA DI correlated with Apo-B/Apo-A1-ratio and Apo-A1. Follow up time after treatment correlated with LVEF (p=0.001). Conclusion: Young asymptomatic CCS exhibit cardiac, vascular, lipid and apolipoprotein changes that could account for increased risk for CVD later in life. These findings emphasize the importance of cardiometabolic monitoring even in young CCS.